Antibiotic resistance in bacteria strains isolated from foods and correlated environments. - Laganà, Pasqualina; Delia, Santi; Di Pietro, Angela; Costa, Alessandro; Coniglio, Maria Anna (Progress in Nutrition, 2020)
Antibiotic resistance is the natural consequence of an evolutionary adaptation of bacteria. The phenomenon is constantly increasing due to the widespread use of antibiotics, not only in human therapy, but also in zootechny and veterinary medicine with the consequent of a rapid selection of antibiotic-resistant strains. Food plays an important role in the development and spread of antibiotic resistance. Antibiotic use in food animals due to treatment, prevention or growth promotion, allows resistant bacteria and resistance genes to pass from food animals to humans through the food chain. The antibiotic resistance of 76 strains from food and from the food sector environment was assessed through the execution of antibiograms carried out with the Kirby-Bauer method. The general results of the sensitivity tests performed on the strains indicated that Gram negative bacteria showed more than 50% of resistance to the 55% of the tested antibiotics (21 resistant strains out of 38 molecules used). Moreover, Gram positive bacteria showed a resistance greater than 50% towards 14% of antibiotics (12 resistant strains out of 32 molecules used). The Authors conclude by hoping for a greater awareness in the use of antibiotics both in the human and veterinary fields.